Photo- and thermally-induced changes in the optical properties of Ge-S-Se amorphous films - Rubish, V.M.; Gera, E.V.; Durcot, M.O.; Pop, M.M.; Kostyukevich, S.O.; Kudryavtsev, A.A.; Mykulanynets-Meshko, O.S.; Rigan, M.Yu. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
The optical transmissions spectra of amorphous Ge-S-Se films of chemical compositions (GeS₂)₅₀(GeSe₂)₅₀ and (GeS₃)₅₀(GeSe₃)₅₀, prepared by thermal evaporation, have been measured over the whole 400 to 800 nm spectral range. It has been ascertained that annealing of the films leads to the absorption edge shift into the short-wave spectral region. The values of pseudo-gap width Eg and film refraction index n have been determined. Changes in optical properties of films are caused by structural transformations taking place in them under laser illumination and annealing.